2009
DOI: 10.2334/josnusd.51.151
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral ossifying fibroma: a case report

Abstract: A case of peripheral ossifying fibroma (POF) in the mandibular gingiva of a 30-year-old man is described. The lesion was asymptomatic, firm, pinkish red and pedunculated histologically showing cellular, fibrous connective tissue stroma with calcified osseous and cementum-like calcifications. Lesions histologically similar to peripheral ossifying fibroma (POF) have been given various names in the existing literature. Therefore, the controversial varied nomenclature and possible etiopathogenesis of peripheral os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 8 publications
2
31
0
12
Order By: Relevance
“…It was also suggested that the crystallinity of the apatites might improve progressively with the development of the lesion, possibly to the same degree as that of bone apatite. 9 An attempt has been made by Endo et al to distinguish cementifying fibromas from ossifying fibromas and fibrous dysplasias by using immunohistochemical analysis for keratan sulfate and chondroitin-4-sulfate, in which the cementifying fibromas showed significant immuno-reactivity for keratan sulfate, and ossifying fibromas and fibrous dysplasias showed intensive immunostaining for chondroitin-4-sulfate. …”
Section: Discussionmentioning
confidence: 99%
“…It was also suggested that the crystallinity of the apatites might improve progressively with the development of the lesion, possibly to the same degree as that of bone apatite. 9 An attempt has been made by Endo et al to distinguish cementifying fibromas from ossifying fibromas and fibrous dysplasias by using immunohistochemical analysis for keratan sulfate and chondroitin-4-sulfate, in which the cementifying fibromas showed significant immuno-reactivity for keratan sulfate, and ossifying fibromas and fibrous dysplasias showed intensive immunostaining for chondroitin-4-sulfate. …”
Section: Discussionmentioning
confidence: 99%
“…Plusieurs dénominations ont été proposées pour cette entité : épulis fibreuse calcifiée, fibrome péri-phérique avec calcifications, fibrome ossifiant périphérique, fibrome cémentifiant périphérique, granulome fibroblastique calcifié, fibrome odontogénique périphérique [5][6][7]. La diversité des termes retrouvés dans la littérature témoigne de la controverse concernant la classification de cette lésion.…”
Section: Commentairesunclassified
“…Plusieurs auteurs suggèrent que ce sont les cellules du ligament parodontal qui sont à l'origine de cette lésion. Cette hypothèse est soutenue par le fait que le FCOP se développe sur la gencive au contact du ligament parodontal, et par la présence de fibres oxytalane dans la trame organique de la masse minéralisée de certains FCOP [1,7]. Un facteur hormonal pourrait jouer un rôle dans la prolifération du FCOP, du fait de sa prédominance chez les femmes en période d'activité génitale [6,9].…”
Section: Commentairesunclassified
See 2 more Smart Citations